Quark mass effects in Higgs production - Michał Czakon; Felix Eschment; Marco Niggetiedt; Rene Poncelet; Tom Schellenberger (Journal of High Energy Physics)
Abstract We examine the effect of finite top- and bottom-quark masses on the Higgs production cross section in the gluon-gluon fusion channel. We employ both MS ¯ $$ \overline{MS} $$ and on-shell renormalisation for the quark masses and provide a thorough comparison. Furthermore, we explore alternative treatments of quark masses, in particular in the four-flavour scheme, and investigate their impact on the cross section. Our work also presents novel predictions for differential cross sections in the Higgs rapidity. The results lead to a significant reduction of scale uncertainties, and our analysis enables us to offer well-grounded recommendations for future research in this area.